2010
DOI: 10.2746/042516406776866291
|View full text |Cite
|
Sign up to set email alerts
|

Minimally invasive plate fixation of lower limb injury in horses: 32 cases (1999-2003)

Abstract: Summary Reasons for performing study: Complications of osteosynthesis including superficial and deep infections continue to affect adversely outcome in equine surgery of the lower limb. Objective: To describe a technique for minimally invasive plate fixation in horses and evaluate clinical results of the technique. Hypothesis: Lower complication rates would occur in horses treated with a minimally invasive approach compared with conventional techniques. Methods: Cases of minimally invasive plate fixation f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
93
2
3

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(105 citation statements)
references
References 26 publications
5
93
2
3
Order By: Relevance
“…Overall return to racing, in the current study is similar to other studies which report return to racing between 25 and 62% . In one report evaluating a lag fashion fixation of propagating condylar fractures under general anaesthesia associated with a long open approach, 14 out of 18 horses returned to training, of which 5 raced .…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Overall return to racing, in the current study is similar to other studies which report return to racing between 25 and 62% . In one report evaluating a lag fashion fixation of propagating condylar fractures under general anaesthesia associated with a long open approach, 14 out of 18 horses returned to training, of which 5 raced .…”
Section: Discussionsupporting
confidence: 87%
“…Despite the low number of cases, this proportion is slightly higher than previously reported . Mean time to first start was also comparable with other studies reporting a return in 11.6–14.5 months .…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…In an earlier review of infection after all types of equine orthopedic surgery, authors identified SSI in 10% of all cases but identified a much higher prevalence in cases that required implants . In several studies specifically examining the clinical use of orthopedic plates for equine lower limb fracture repair or arthrodesis, SSI was identified in 32%–80% of cases …”
Section: Introductionmentioning
confidence: 99%
“…This technique was used for articular debridement because the advanced osteoarthritis precluded adequate flexion of the joints for effective arthroscopic debridement. A 2‐cm skin incision was made over the proximal dorsolateral aspect of the third metacarpal bone, and a plate passer was used to create a subcutaneous tunnel over the dorsolateral aspect of the carpus to facilitate placement of the plate . The first plate was contoured to the limb by using fluoroscopic guidance.…”
Section: Clinical Reportsmentioning
confidence: 99%